Learning Independence: How Correlation is the Innovation of PAI Learning through the Digital Literacy Program? - Fauzi, Akbar; Khasanah, Uswatun; Sada, Heru Juabdin; Bahri, Syaiful; Octafiona, Era; Azizah, Nurul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research stems from the importance of understanding the influence of digital literacy on students’ learning independence. The primary objective of this study is to analyze the extent to which the implementation of digital literacy correlates with the learning independence of students in Islamic Education (PAI). A quantitative approach with an ex-post facto design method was employed in this study. The research subjects consisted of 81 PAI students at UIN Raden Intan Lampung. Data were collected through questionnaires and analyzed using various statistical tests, including normality tests, homogeneity tests, heteroscedasticity tests, linearity tests, T-tests, determination coefficient tests, and F-tests. The findings indicate a positive relationship between the application of digital literacy and students’ learning independence, as evidenced by an F-test value of 0.001 and a T-test value of 0.000. These findings highlight the significant role of digital literacy in enhancing students’ learning independence. The positive results underscore the importance of digital literacy as a factor that can strengthen and support the development of learning independence, which is a critical aspect of higher education.